Digitalisasi Data Permukiman Jorong Korong Lambah Menggunakan Platform Google My Maps - Juana Wangsa Putri; Bidara Lidya Irfan; Luthfi Zaki; Meisaroh Indah Krisna; Muhammad Fakhrul Zuhdi; Nabilah Durrotul Hikmah; Wahyu Saputra (CV. ITTC INDONESIA, 2026)
Digitalization of settlement data in Jorong Korong Lambah, Nagari Batu Bajanjang, West Sumatra,is crucial due to the absence of integrated spatial visualization to support regional planning. The primary challenge faced is the limited access to accurate settlement data for village officials. This community service project aims to map settlement layouts participatively using the accessible and free Google My Maps platform. The methods applied include field observations, coordinate data collection (geospatial surveys), and training sessions on platform utilization for local cadres. The results demonstrate the creation of an interactive digital map displaying facilities,boundaries, and residential distributions in real-time. In conclusion, this digitalization successfully establishes geospatial-based data independence at the nagari level, serving as an important instrument for decision-making and transparencyin rural settlement management.